Cancer incidence in eighteen cities of the State of São Paulo, Brazil Incidência de câncer em dezoito cidades do Estado de São Paulo - Gisela I Andreoni; Donaldo B Veneziano; Osvaldo Giannotti Filho; Carlos Marigo; Antonio P Mirra; Luiz Augusto M Fonseca (Universidade de São Paulo, 2001)
OBJECTIVE: As in Brazil cancer registries are mostly based on large cities, there are no estimates per state or per region and information on the disease incidence in the vast in-land areas is very scarce. An incidence survey was conducted in 18 major cities of the state of São Paulo, excluding the capital, aiming to collect information about cancer incidence in the state of São Paulo. METHODS: Of the 18 cities in state of São Paulo included in the survey, all had available resources for cancer management. Data from the year of 1991 were collected by the personnel of the Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Statistics), who were especially trained by the study coordinators at the Fundação Oncocentro de São Paulo (Cancer Center of São Paulo). The collected data were processed and analyzed at the Oncocentro. Data collection, processing, and analyses were performed according to the recommendations of the International Agency for Research on Cancer. RESULTS: Although some discrepancies were observed in cancer incidence rates between the cities, results obtained for all 18 cities combined were remarkably close to those recently found for the city of São Paulo in the year 1993. One remarkable finding was the relatively high cancer incidence rates in both sexes in the city of Santos. CONCLUSIONS: The very similar all-sites cancer incidence rates found in the year 1991, when compared to those for the city of São Paulo in the year 1993, are suggestive that all regions have common cancer-related factors. Nevertheless, other explanations, such as the inclusion in the study of prevalent cases, as well as of non-residents, may have occurred in both studies, biasing the results. There is a need of further studies to confirm the high cancer incidence in Santos. OBJETIVO: Os registros populacionais de câncer no Brasil são invariavelmente baseados em cidades grandes. Não existem registros de câncer em que a abrangência inclua Estados ou regiões e em que os achados possam refletir mais fielmente a incidência da doença no interior do País. Com base nessa percepção, foi realizado estudo sobre a incidência de câncer em 18 cidades do interior do Estado de São Paulo, visando a dimensionar a importância da doença nessa região brasileira. MÉTODOS: Das 18 cidades do interior do Estado de São Paulo incluídas no estudo, duas não eram sede de região administrativa, e todas contavam com recursos para diagnóstico e tratamento de câncer. O ano escolhido para ser pesquisado foi 1991. A coleta de dados foi realizada por equipes do Instituto Brasileiro de Geografia e Estatística, especialmente treinadas pelo pessoal técnico da Fundação Oncocentro de São Paulo; nesta última, as informações foram processadas e analisadas. Os procedimentos adotados para a coleta e análise dos dados seguiram as recomendações da International Agency for Research on Cancer . RESULTADOS: Apesar das discrepâncias observadas nas taxas de incidência de câncer entre as cidades componentes do estudo, os resultados obtidos no conjunto das 18 cidades mostraram-se próximos aos apurados pelo registro populacional de câncer do Município de São Paulo em 1993. Ressaltaram-se as altas taxas de incidência de várias formas de câncer tanto no sexo feminino quanto masculino, na cidade de Santos. CONCLUSÕES: A similitude das taxas de incidência de câncer (todas as localizações combinadas) entre o Município de São Paulo em 1993 e o conjunto das 18 cidades pesquisadas neste estudo parece sugerir a existência de fatores genéticos e ambientais em comum, influindo na gênese da doença nessas populações; no entanto, outras razões podem igualmente ser aventadas, como a inclusão de casos prevalentes e de não-residentes em ambos os estudos. As altas taxas de incidência registradas para quase todas as formas de câncer em Santos necessitam ser confirmadas em novos estudos.